Fast Distance Protection for Proximal Fault of EHV Transmission Line - Li Zhenkun; Ji Hui; Fu Yang (Institute of Advanced Engineering and Science, 2013)
As the full length is considered in the traditional EHV line protection, proximal circuit fault can’t be moved in an ideal short time. A fast distance protection algorithm for proximal fault of EHV transmission line is proposed in the paper. Based on differential equation model and power frequency variation principle, the method has fast response speed and small workload. And the protection for proximal fault of long distance EHV transmission lines can be correctly implemented in a very short time. The method is realized with a low pass prefilter and without digital filter. Finally, through the RTDS simulation platform, a variety of fault modes of 500kV transmission lines is realized, and the accuracy and rapidity of the algorithm is verified by the simulation result. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1984